Food Parenting Practices Promoted by Childcare and Primary Healthcare Centers in Chile: What Influences Do These Practices Have on Parents? A Qualitative Study - Paulina Molina; María José Coloma; Patricia Gálvez; María José Stecher; Marcela Vizcarra; Andiara Schwingel (MDPI AG, 2023)
Chile, like many other countries in the world, is experiencing a high prevalence of childhood overweight. Among the factors influencing children's eating behaviors are the food parenting practices promoted by community organizations. More information is needed on the influences of these recommendations on the parenting practices of parents of preschoolers. This study examined what types of food parenting practices are promoted in childcare and primary healthcare centers and how these recommendations influence subsequent parental behavior. Interviews using photo-elicitation were conducted with 25 parents of Chilean preschoolers. The interviews were analyzed using inductive thematic analysis. Five themes were identified to describe food parenting practices promoted by community organizations and the influences that these practices had on parents of preschoolers. Healthcare centers were found to educate parents and provided a structured feeding. However, parents found their advice regarding dietary restriction challenging to follow. Childcare centers also provided information about healthy diet, food monitoring, and diversifying the child's diet in a way that was perceived as adequate. While childcare centers encouraged structured and autonomous food parenting practices in a positive and supportive manner, healthcare centers tended to provide more restrictive guidance that posed challenges for parents struggling with preschool nutritional care.